Analysis of E-Learning Activities as School Learning Media in the Era of Society 5.0 Using Big Data - Irika Widiasanti; Dea Astriani; Asyifa Eka Rahayanti; Bagus Septianto; Linda Widianingsih (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
To prepare the community to face Society 5.0, cooperation is needed from various parties, including the education sector. The development of the education sector is crucial today, as it provides optimal and quality educational services and facilitates technological advancements. Regarding educational technology, a system utilized to support learning and achieve desired outcomes, it is important to associate it with the Society 5.0 era. One form of technological development in education that can be used as a learning medium is e-learning. This research adopts a quantitative approach. The research subjects consist of secondary data from a Kaggle dataset titled "Students Adaptability Level in Online Education," which was collected by Md. Aktaruzzaman Pramanik and Nishat Ahmed Samrin. The data includes 530 students who participated in online learning at schools. The results of this research indicate that the development of information technology in the Society 5.0 era can be utilized by the education sector, such as through e-learning as a learning medium. The impact of these research findings can be observed in the quality of education in Indonesia, where all aspects of life coexist with digital media.